Biotic and environmental changes in the Panthalassa Ocean across the Norian (Late Triassic) impact event - Honami Sato; Yutaro Takaya; Kazutaka Yasukawa; Koichiro Fujinaga; Tetsuji Onoue; Yasuhiro Kato (Progress in Earth and Planetary Science, 2020)
Abstract Stratigraphic records of impact ejecta preserved in a pelagic deep-sea setting occur within Upper Triassic successions of the subduction-generated accretionary complexes of central Japan. A significant biotic turnover in radiolarians occurred during the ~ 300 kyr time interval after the impact event, which is characterized by a remarkable reduction in the burial flux of radiolarian silica. However, the nature of the environmental conditions at this time remains unclear. To investigate the environmental changes that triggered a decline in radiolarian burial flux after the impact event, geochemical proxies (major, trace, and rare earth elements) were applied to the middle–upper Norian (Upper Triassic) bedded chert succession of the Mino Belt, central Japan. A progressive environmental deterioration is evident from (1) a post-impact shutdown of burial flux of primary and silica- and apatite-secreting organisms; and (2) a subsequent abrupt increase in chemical weathering associated with a sustained reduction in the burial flux of radiolarian silica. No significant redox changes were observed across the impact event. The continental weathering proxies suggest a transient increase in weathering intensity occurred during the decline of radiolarian burial flux, likely in response to a short-term warm and humid period. Our results delineate a remarkable record of progressive environmental changes in the Panthalassa Ocean after this large impact event.